OP0307 Inhibitory Effects of IL-17 on Chondrogenic Differentiation of Human Mesenchymal Stem Cells Through the Phosphorylation of Sox9. (23rd January 2014) - Kondo, M.; Yamaoka, K.; Sonomoto, K.; Fukuyo, S.; Oshita, K.; Okada, Y.; Saito, K.; Tanaka, Y.
Abstract : Background: Mesenchymal stem cells (MSCs) are multipotent cells that are able to differentiate into chondrocytes. Existence of MSCs in the articular cartilage suggests the contribution of MSCs to cartilage homeostasis with intrinsic ability to repair cartilage defect. However, under inflammatory condition such as rheumatoid arthritis (RA), chondrogenic defect is commonly observed. Recently, IL-17 has gathered attention as a key cytokine that has distinct role in chronic inflammation inducing cartilage matrix breakdown and chondrocytes apoptosis in RA. However, the effects of IL-17 on chondrogenic differentiation remain unclear. Objectives: Aim of this study is to clarify the effects of IL-17 on chondrogenic differentiation of human MSCs. Methods: Human bone marrow MSCs were pellet cultured in chondrogenic induction medium containing TGF-b3. The accumulation of cartilage matrix molecules, proteoglycans and type II collagen (Col2), were determined by staining with Safranin O and anti-Col2 antibody. Chondrogenic markers ( Col2a1 / Aggrecan / Col10a1 / Alkaline phosphatase ) and IL-17 receptor A ( IL-17RA ) expressions were evaluated by real-time PCR. Results: IL-17 receptor expression was marginal in undifferentiated MSCs, but it was induced during the first 2 days of chondrogenic culture. The elevations of cartilage matrix and chondrogenic marker gene expressions in the aggregates on day 21 were inhibited by the addition of IL-17 to the culture in a dose-dependent manner. The expression and phosphorylation of Sox9, the master regulator of chondrogenesis, were increased by the chondrogenic culture and Sox9 phosphorylation was sustained up to day 21. Although the total Sox9 expression was not altered by IL-17, phosphorylated Sox9 was significantly decreased by IL-17 at day 7. The activity of cAMP-dependent protein kinase A (PKA), a kinase known to phosphorylate Sox9, was increased in the aggregates during chondrogenesis and suppressed by IL-17. Addition of H89, a PKA inhibitor, suppressed Sox9 phosphorylation and resulted in considerable inhibition of cartilage matrix accumulation and chondrogenic marker gene expressions in the aggregates. Conclusions: We have demonstrated that IL-17 inhibited chondrogenic differentiation of human MSCs through the inhibition of Sox9 phosphorylation, which was potentially involved by the suppression of PKA activity. These results suggest that IL-17 induces cartilage disorder by disrupting homeostasis and self-repair function of MSCs. Thus, anti-IL-17 antibody treatment may lead to recovery of self-repair ability. Considering the cell based therapy with MSCs, preoperative inactivation of IL-17 in the joint of RA patients should be important for the clinical settings. Disclosure of Interest: M. Kondo Employee of: Mitsubishi-Tanabe Pharma Co., Ltd., K. Yamaoka: None Declared, K. Sonomoto: None Declared, S. Fukuyo: None Declared, K. Oshita Employee of: Mitsubishi-Tanabe Pharma Co., Ltd., Y. Okada: None Declared, K. Saito: None Declared, Y. Tanaka Grant/research support from: Bristol-Myers Squibb, MSD K.K., Chugai Pharma Co., Ltd., Mitsubishi-Tanabe Pharma Co., Ltd., Astellas Pharma Inc., Abbott Japan Co., Ltd., Eisai Co., Ltd. and Janssen Pharmaceutical K.K., Speakers bureau: Mitsubishi-Tanabe Pharma Co., Ltd., Abbott Japan Co., Ltd., Eisai Co., Ltd., Chugai Pharma Co., Ltd., Janssen Pharma K.K., Santen Pharma Co., Ltd., Pfizer Japan Inc., Astellas Pharma Inc., Daiichi-Sankyo Co., Ltd., GlaxoSmithKline K.K., Astra-Zeneca, Otsuka Pharma Co., Ltd., Actelion Pharma Japan Ltd., Eli Lilly Japan K.K., Nippon Kayaku Co., Ltd., UCB Japan Co., Ltd., Quintiles Transnational Japan Co. Ltd., Ono Pharma Co., Ltd.,